2008
DOI: 10.1002/lt.21540
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coronary artery calcification in patients undergoing assessment for orthotopic liver transplantation

Abstract: Patients with advanced liver disease are at increased risk of cardiovascular events, especially following orthotopic liver transplantation (OLT). Coronary artery calcification (CAC) is a novel and independent predictor of cardiovascular risk, but its prevalence and utility in patients with cirrhosis are unknown. The aim of this study was to define the prevalence of CAC and its association with markers of disease severity and standard measures of cardiovascular risk in a large cohort of patients undergoing OLT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 35 publications
2
47
1
Order By: Relevance
“…A recent study [101] of 101 cirrhotic patients showed a strong relationship between the CACS and a number of specific cardiovascular risk factors. In this study, the CACS revealed a high prevalence of occult coronary artery disease in patients undergoing LT assessment.…”
Section: Computed Tomographymentioning
confidence: 99%
“…A recent study [101] of 101 cirrhotic patients showed a strong relationship between the CACS and a number of specific cardiovascular risk factors. In this study, the CACS revealed a high prevalence of occult coronary artery disease in patients undergoing LT assessment.…”
Section: Computed Tomographymentioning
confidence: 99%
“…DSE was positive in 7.5% of patients and had a high sensitivity and specificity for CAD in this cohort, but the number of patients studied was small. A study of coronary artery calcium scores in 101 liver transplantation candidates found an elevated coronary artery calcium score in 74% of asymptomatic patients, 288 with 37.6% having scores in the moderate-risk range (Ͼ100, or Ϸ2% predicted annual risk of cardiac events) and 19.8% having scores in the high-risk range (Ͼ400, or Ϸ3% to 5% predicted annual risk of cardiac events). 289 There is considerable concern about the efficacy and cost-effectiveness of the screening strategy used for CAD identification before liver transplantation.…”
Section: Evaluation For Cad In Liver Transplantation Candidatesmentioning
confidence: 99%
“…Whether nonalcoholic steatohepatitis cirrhosis is an independent CAD risk factor with incremental predictive value over these traditional risk factors remains to be determined (26 -28). Coronary calcium is also strongly associated with traditional CAD risk factors in the cirrhotic population (29). In addition, concomitant renal dysfunction in the setting of ESLD is associated with increased cardiovascular risk (30).…”
Section: Coronary Artery Diseasementioning
confidence: 99%